Intramolecular Borylation via Sequential B−Mes Bond Cleavage for the Divergent Synthesis of B, N, B‐Doped Benzo[4]helicenes. Issue 8 (16th January 2020) - Knöller, Julius A.; Meng, Guoyun; Wang, Xiang; Hall, David; Pershin, Anton; Beljonne, David; Olivier, Yoann; Laschat, Sabine; Zysman‐Colman, Eli; Wang, Suning
Abstract: New symmetric and unsymmetric B, N, B‐doped benzo[4]helicenes 3 –6 a/b have been achieved in good yields, using a three‐step process, starting from N(tolyl)3 in a highly divergent manner (7 examples). A borinic acid functionalized 1, 4‐B, N‐anthracene 1 was found to display unprecedented reactivity, acting as a convenient and highly effective precursor for selective formation of bromo‐substituted B, N, B‐benzo[4]helicenes 2 a /2 b via intramolecular borylation and sequential B−Mes bond cleavage in the presence of BBr3 . Subsequent reaction of 2 a /2 b with Ar‐Li provided a highly effective toolbox for the preparation of symmetrically/unsymmetrically functionalized B, N, B‐helicenes. Their high photoluminescence quantum yields along with the small Δ E ST suggest their potential as thermally activated delayed fluorescence (TADF) emitters for organic light‐emitting diodes (OLEDs). Abstract : A new and divergent intramolecular borylation method has been found to be highly effective for the synthesis of a variety of symmetrically and unsymmetrically functionalized B, N, B‐[4]helicenes with potential applications as thermally activated delayed fluorescence (TADF) emitters in organic light‐emitting diodes (OLEDs). EDG/EWG=electron‐donating/‐withdrawing group, Mes=Mesityl.